Discover a wealth of knowledge at Westonci.ca, where experts provide answers to your most pressing questions. Discover solutions to your questions from experienced professionals across multiple fields on our comprehensive Q&A platform. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

find the solutions for this polynomial equation 3(x − 2)(x2 − 9)(x + 7) = 0

Sagot :

Answer: If the x2-9 is x^2-9, then this is the answer. If not and it's supposed to be 2x then the answer is x=2 or x=−7 or x=9/2

Step-by-step explanation:

3(x−2)(x2−9)(x+7)=0

3x4+15x3−69x2−135x+378=0

Step 1: Factor left side of equation.

3(x−2)(x+3)(x−3)(x+7)=0

Step 2: Set factors equal to 0.

x−2=0 or x+3=0 or x−3=0 or x+7=0

x=2 or x=−3 or x=3 or x=−7